ESCRT-III mediated cell division in Sulfolobus acidocaldarius – a reconstitution perspective - Härtel, Tobias; Schwille, Petra (Frontiers in Microbiology, 2014)
In the framework of Synthetic Biology, it has become an intriguing question what would be the minimal representation of cell division machinery. Thus, it seems appropriate to compare how cell division is realized in different microorganisms. In particular, the cell division system of Crenarchaeota lacks certain proteins found in most bacteria and Euryarchaeota, such as FtsZ, MreB or the Min system. The Sulfolobaceae family encodes functional homologs of the eukaryotic proteins Vps4 and ESCRT-III. ESCRT-III is essential for several eukaryotic pathways, e.g. budding of intralumenal vesicles (ILVs), or cytokinesis, whereas Vps4 dissociates the ESCRT-III complex from the membrane. CdvA (Cell Division A) is required for the recruitment of crenarchaeal ESCRT-III proteins to the membrane at mid-cell. The proteins polymerize and form a smaller structure during constriction. Thus, ESCRT-III mediated cell division in S. acidocaldarius shows functional analogies to the Z ring observed in prokaryotes like E. coli, which has recently begun to be reconstituted in vitro. In this short perspective, we discuss the possibility of building such an in vitro cell division system on basis of archaeal ESCRT-III.